The Effect of Nicotine Dependence on Psychopathology in Patients with Schizophrenia - Yee, A.; Mohamed, N.N.N.; Hashim, A.H.; Loh, H.S.; Singh, M.K.H.; Ng, C.G.; Jambunathan, S.T. (Hindawi Publishing Corporation, 2015)
Introduction. Our study aims to determine the prevalence of nicotine dependence and investigate the effect of nicotine dependence on psychopathology among schizophrenia patients. Methods. A cross-sectional study was carried out in an outpatient psychiatric clinic at a general hospital in Malaysia. 180 recruited subjects were administered the Malay version of Mini International Neuropsychiatric Interview (MINI), the Positive and Negative Symptom Scale (PANSS), and the Malay version of Fagerstrom Test for Nicotine Dependence (FTND-M) questionnaires. Results. The prevalence of nicotine dependence among the subjects was 38.1% () and they were mainly composed of male gender, Malay ethnicity, being treated with atypical antipsychotics, and taking other illicit drugs or alcohol. Subjects with severe nicotine dependence scored less in the negative subscale of PANSS compared with the nonsmokers (). On performing the hierarchy multiple regressions, dependence status still significantly predicted negative scores after adjusting the confounders (, ). Conclusion. The rate of nicotine use disorder among schizophrenia patients in this study is higher than that of the general population in Malaysia. The significant association between nicotine dependence and negative psychopathology symptoms will help the healthcare practitioners in their management of nicotine dependence among schizophrenia patients.